ผลกระทบที่ประเทศไทยจะได้รับในการเข้าเป็นภาคีธรรมนูญศาลอาญาระหว่างประเทศ : ศึกษากรณีความร่วมมือระหว่างประเทศและการส่งผู้ร้ายข้ามแดน - อัญชิสา เต็มพงศ์พัฒนา (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The objective of this research is to study the Rome Statute of International Criminal Court which established the jurisdiction over persons for the most serious crimes of international concern. Since long time the persons who committed serious crimes often have had impunity or amnesty themselves. This International Criminal Court has the objective to have jurisdiction on those persons with the pre - condition that the State which has jurisdiction over the case unwilling or unable to exercise the jurisdiction. For the reasons that the most serious crimes of concern to the international community as a whole must not go unpunished and that their effective prosecutions must be ensured by measures at the national level and by enhancing international cooperation, the establishment of International Criminal Court had the majority vote in the diplomatic conference concludes for the Rome Statute of International Criminal Court. The Rome Statute is subjected to ratification, acceptance or approval by 60 ratification States before entry into force. Thailand has also joined in that diplomatic conference and has been one of the signatory states. Going to be a ratification state, Thailand will consider and evaluate all obligations setting up by the Rome statute including the obligation to corporate to The Court. Not only the obligation to corporate on mutual legal assistance and extradition, Thailand shall review the extradition law for corporation with the International Organization but also consider to all forms of law because there are more law impacts concerning this matter, such as ะ the immunity of the Head of State, the jurisdiction of Thai Court 1the procedures for developing and improving Thai law in accordance with the Rome Statute and the State security. Thailand should have to consider and analyze for all impacts before going to be the membership of the Rome Statute of International Criminal Court.